Bureaucratic Recruitment Trends : A Systematic Literature Review (SLR) - Naila Febrina Akmalia; Lira Vira Anatasya; Yasmine Zulfa Almadhea (LPPM STISIP IMAM BONJOL, 2025)
This study aims to analyze trends in bureaucratic recruitment in optimizing the performance of state apparatus in the era of modern governance. The research method used is a systematic literature review of 83 scientific articles sourced from the Scopus database, analyzed using the Vosviewer application. The results of the study indicate a global trend toward reforming the bureaucratic recruitment system, emphasizing meritocracy, digital competence, and adaptability to social change. The analyzed studies suggest that a recruitment approach based on merit systems, transparency, and the use of digital technology can improve the quality of civil service human resources and promote the creation of a bureaucracy responsive to public needs. With the development of digital society and the globalization of public administration, many countries have begun to integrate e-recruitment-based systems to accelerate the selection process, minimize nepotism, and expand the reach of quality talent. The limitation of this study is that the articles used are only sourced from the Scopus database, so the findings may not comprehensively describe global issues related to public service in the digital era. Future research should utilize scientific articles from other reputable international databases, such as Web of Science and Dimensions Scholars.